Genetic modifiers of respiratory function in Duchenne muscular dystrophy. Issue 5 (28th April 2020) - Bello, Luca; D'Angelo, Grazia; Villa, Matteo; Fusto, Aurora; Vianello, Sara; Merlo, Beatrice; Sabbatini, Daniele; Barp, Andrea; Gandossini, Sandra; Magri, Francesca; Comi, Giacomo P.; Pedemonte, Marina; et al.
Abstract: Objective: Respiratory insufficiency is a major complication of Duchenne muscular dystrophy (DMD). Its progression shows considerable interindividual variability, which has been less thoroughly characterized and understood than in skeletal muscle. We collected pulmonary function testing (PFT) data from a large retrospective cohort followed at Centers collaborating in the Italian DMD Network. Furthermore, we analyzed PFT associations with different DMD mutation types, and with genetic variants in SPP1, LTBP4, CD40, and ACTN3, known to modify skeletal muscle weakness in DMD. Genetic association findings were independently validated in the Cooperative International Neuromuscular Research Group Duchenne Natural History Study (CINRG‐DNHS). Methods and Results: Generalized estimating equation analysis of 1852 PFTs from 327 Italian DMD patients, over an average follow‐up time of 4.5 years, estimated that forced vital capacity (FVC) declined yearly by −4.2%, forced expiratory volume in 1 sec by −5.0%, and peak expiratory flow (PEF) by −2.9%. Glucocorticoid (GC) treatment was associated with higher values of all PFT measures (approximately + 15% across disease stages). Mutations situated 3' of DMD intron 44, thus predicted to alter the expression of short dystrophin isoforms, were associated with lower (approximately −6%) PFT values, a finding independently validated in the CINRG‐DNHS. Deletions amenable to skipping of exon 51 and 53 were independently associated with worse PFT outcomes. A meta‐analysis of the two cohorts identified detrimental effects of SPP1 rs28357094 and CD40 rs1883832 minor alleles on both FVC and PEF. Interpretation: These findings support GC efficacy in delaying respiratory insufficiency, and will be useful for the design and interpretation of clinical trials focused on respiratory endpoints in DMD.